Health economics aspects of kidney transplantation in Sicily: a benchmark analysis on activity and estimated savings - Cacciola, Roberto; Leonardis, Francesca; Gitto, Lara; Favi, Evaldo; Gruttadauria, Salvatore; Clancy, Marc; Veroux, Massimiliano; Angelico, Roberta; Pagano, Duilio; Mazzeo, Carmelo; Cacciola, Irene; Santoro, Domenico; et al. (Frontiers in Public Health, 2023)
Publication costs were funded by Grant Ricerca Corrente, Italian Ministry of Health.Studies on the health economics of kidney transplantation (KT) have strengthened the highly successful clinical practice observed over the recent decades, demonstrating that the established cost-effectiveness actually extends into substantial savings for the healthcare services. In our study we produce an estimate of the financial benefits of KT applying the Kidney Transplant Coefficient of Value to the KT activity performed in our region. The subsequent benchmark analysis identified the volume of activity and estimated financial savings based on a tool that may serve to encourage growth strategies in KT beyond the boundaries of the regional program that we have analysed. Evidence presented through the application of a novel health economics tool, as suggested in our study may also contribute in defining adequate growth strategies beyond the boundaries of the regional program that we have analysed. In the context of current financial uncertainty and global instability, the clinical and financial considerations arising from the study may offer a valid support to decision makers of any regional or national health care service, while contributing to structure future dialogues between the wider transplant community and service commissioners.